FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN INVESTOR SAHAM SYARIAH DI INDONESIA TAHUN 2015-2021 - Mustaharuddin Mustaharuddin; Habrianto Habrianto; Dharma Putra (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
Factors Influencing Economic Growth on the Growth of Sharia Stock Investors in Indonesia in 2015-2021 Stocks have recently been increasingly in demand by the majority of people in Indonesia, many phenomena have occurred including economic problems, crises, politics, and others, but these fluctuations do not affect people's interest in buying Islamic stocks. This study aims to determine the effect of the dollar exchange rate, inflation, and economic growth on the growth of stock investors in Indonesia. This type of research is descriptive research which is analyzed using quantitative analysis. The data used are the financial reports of Islamic banks in Jambi through the Financial Services Authority (OJK), in the period from March 2015 to December 2021. The prerequisite analysis test was carried out using the normality test, muticolinierity, heteroscedasticity, and linearity tests. Furthermore, the data were analyzed using multiple linear regression analysis. Based on the results of the study, it can be concluded that during the period from 2015 to December 2021, the dollar exchange rate has no significant effect on the growth of Islamic stock investors and inflation has a significant negative effect on the growth of Islamic stock investors in Indonesia, GRDP has a significant effect on the growth of stock investors in Indonesia. and simultaneously the Dollar Exchange Rate, Inflation, and Economic Growth are significant for the Growth of Stock Investors in Indonesia.